Preparation method of graphene oxide coated natural graphite negative electrode material

Graphene oxide is coated on natural graphite by liquid phase coating spray drying to form a "core-shell" structure, which solves the problems of poor compatibility between natural graphite and electrolyte and high energy consumption of high temperature carbonization, and achieves high materials The improvement of cycling performance and high-current charging and discharging performance is suitable for large-scale production.

CN119284894AInactive Publication Date: 2025-01-10HANGZHOU INST OF ADVANCED MATERIAL BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411379104.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the application of natural graphite negative electrode materials in lithium-ion batteries has problems with graphite layer peeling caused by poor compatibility with electrolytes and prone to co-embedding of solvated lithium ions, resulting in poor circulation performance and high-temperature carbonization. High energy consumption in the process and complex process.

Method used

Using liquid phase coating spray drying method, graphene oxide is used as a coating agent, graphene oxide is dissolved by ultrasonic and mixed with natural graphite evenly, and a peristaltic pump is used to suck it into a spray dryer for drying to prepare graphene oxide coated natural stone The ink negative electrode material forms a "core-shell" structure, improving the material's cyclic stability and high-current charging and discharging performance.

Benefits of technology

The process flow is simplified, energy consumption is reduced, the electrochemical performance and cycle stability of the material are improved, and the co-embedding of solvated lithium ions and graphite layer peeling problems are avoided, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284894A_ABST
    Figure CN119284894A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a graphene oxide coated natural graphite negative electrode material, and belongs to the technical field of lithium ion batteries. According to the method, graphene oxide is used as a coating agent, natural graphite is used as a raw material, and a spray drying method is used for preparing the high-performance lithium ion battery negative electrode material. The preparation method comprises the following steps: firstly, preparing graphene powder and a solvent into dispersion liquid according to a certain proportion, then uniformly mixing the dispersion liquid with natural graphite according to a certain proportion, and finally, controlling spray drying parameters to obtain the graphene-coated natural graphite negative electrode material. The graphene is adopted as a coating agent, the natural graphite negative electrode material is coated to form a core-shell structure, the core-shell structure is good in compatibility with an electrolyte, stripping of a graphite layer caused by co-intercalation of solvated lithium ions is avoided, meanwhile, volume expansion of natural graphite electrode particles in the charging and discharging process is buffered, and the performance of the lithium ion battery is improved. And the cycle performance and the high-current charge-discharge performance of the natural graphite are greatly improved. The method has the advantages of simple process, low cost and good product coating effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a graphene oxide-coated natural graphite negative electrode material and application of the material in lithium ion batteries, belonging to the technical field of lithium ion batteries. Background Art

[0002] With the rapid development of society, non-renewable energy is decreasing, energy crisis is becoming more and more prominent, and environmental pollution is becoming more and more serious. Therefore, human beings urgently need to develop clean new energy. Since the advent of lithium-ion batteries in the early 1990s, they have been widely used in electronic products and other fields due to their advantages such as high output voltage, long cycle life, low self-discharge rate, no memory and green environmental protection. With the development trend of automobile electrification, lithium-ion batteries have a very broad prospect.

[0003] As a very important negative electrode material for lithium batteries, natural graphite has many advantages, such as low charge and discharge voltage platform and high specific capacity. However, there are also many problems, such as poor compatibility with electrolyte, easy peeling of graphite layer caused by co-embedding of solvated lithium ions, and ultimately poor battery cycle performance. The existence of these problems affects the application of natural graphite in high-end products. Therefore, we need to modify the natural graphite negative electrode material.

[0004] At present, the main modification methods are: mechanical grinding, surface oxidation, coating modification and doping modification, among which coating modification is a commonly used method for natural graphite negative electrode materials. The document "Spherical natural graphite coated by a thick layer of carbonaceous mesophase for use as an anode material in lithium ion batteries (Journal of applied electrochemistry, 2009, 39 (7): 1081-1086)" uses natural spherical graphite and coal tar pitch as raw materials and obtains a carbon-coated natural graphite material by high-temperature carbonization. After coating, the first coulomb efficiency of the asphalt-coated natural graphite is increased by 5%, and it exhibits good cycle stability and rate performance. The document "Phenolic resin coated oxidized natural graphite as negative electrode material for lithium ion batteries (Acta Physico-Chimica Sinica, 2011, 27 (9): 2129-2134)" coats phenolic resin on the surface of natural graphite, and then performs high-temperature carbonization treatment to prepare a carbon-coated oxidized natural graphite negative electrode material with a "core-shell" structure. Patent CN111081989A adds high softening point asphalt and spherical natural graphite into a VC mixer, mixes thoroughly for 40-50 minutes, then takes out the mixed materials and puts them into a graphite crucible, sends them into a high sand kiln, and passes N2 protection in the kiln. The temperature is raised to 1040-1060℃ and kept warm for 3-4 hours. After the sample is carbonized, it is taken out and mechanically dispersed by a disperser. After completion, the material is sieved through a 200-mesh sieve to obtain asphalt-coated spherical natural graphite. This method is simple, fast, and easy to operate. The prepared asphalt-coated spherical natural graphite negative electrode material has a high reversible capacity and good cycle performance, and can be prepared on a large scale. In summary, most of these research works use asphalt or hard carbon materials to coat natural graphite. Although the coated spherical natural graphite negative electrode material has a high reversible capacity and good cycle performance, the entire process is complicated, requires high-temperature carbonization, and has high energy consumption. Therefore, finding new materials, reducing energy consumption, and simplifying the process are currently a difficult problem that needs to be solved urgently in academia and industry. Graphene has a unique two-dimensional crystal structure and good conductivity. Coating it on natural graphite negative electrode materials is beneficial to improving the cyclic stability of the material. Patent CN108281634A ultrasonically mixes graphene oxide aqueous solution with graphite, then removes the solvent to obtain a dry solid powder, and finally treats it at 600-1400℃ for 1-4h under an inert atmosphere, and cools to obtain a graphene-coated lithium-ion battery graphite negative electrode material. This method has good coating effect and high purity, but it needs to reduce graphene oxide under high temperature conditions later, which consumes a lot of energy.By improving the coating process and utilizing the flexible structure of graphene, graphene can be coated on the surface of natural graphite to improve the electrochemical properties of natural graphite, which is of great significance for the application of natural graphite in high-end products. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention aims to provide a method for preparing a graphene oxide-coated natural graphite negative electrode material by using graphene oxide as a coating agent through a liquid phase coating spray drying method.

[0006] The technical solution used in the present invention is a method for preparing a graphene-coated natural graphite negative electrode material, and the specific steps are as follows:

[0007] Step (1) ultrasonically dissolving a certain mass of graphene powder in a solvent to obtain graphene dispersions of different concentrations;

[0008] Step (2) mixing the natural graphite raw material and the graphene dispersion liquid in a certain proportion to obtain a mixed liquid;

[0009] Step (3) The mixed solution obtained in step (2) is sucked into a spray dryer using a peristaltic pump, and dried at a certain temperature and atomization frequency to obtain a graphene-coated natural graphite negative electrode material.

[0010] Preferably, the number of graphene layers in step (1) is 1-3, the diameter of the layer is 0.5-20 um, and the thickness is 0.5-3 nm.

[0011] Preferably, the concentration of the graphene solution in step (1) is 0.1-2.5 mg / mL.

[0012] The present invention has the following advantages:

[0013] (1) This method adopts liquid coating spray drying method, which has the advantages of simple preparation process, low cost, no pollution, and is suitable for large-scale production.

[0014] (2) This method uses graphene with a flexible structure as a coating agent to coat natural graphite to form a "core-shell" structure, and the coating effect is good.

[0015] (3) The samples prepared by this method have a "core-shell" structure and good compatibility with the electrolyte, avoiding the peeling problem of the graphite layer caused by the co-embedding of solvated lithium ions. At the same time, it buffers the volume expansion of natural graphite particles during the charging and discharging process, greatly improving the cycle performance and high-current charging and discharging performance of natural graphite. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope image of the graphene-coated natural graphite negative electrode material prepared in Invention Implementation Example 1.

[0017] Figure 2 The cycling performance curve of the graphene-coated natural graphite negative electrode material prepared in Invention Implementation Example 1 at a current density of 0.2C.

[0018] Figure 3 The rate performance curve of the graphene-coated natural graphite negative electrode material prepared in Invention Implementation Example 1 at different current densities.

[0019] Specific implementation examples

[0020] The present invention is further described below by way of implementation, but is not intended to limit the present invention.

[0021] Example 1

[0022] 0.05 g of graphene oxide was dissolved in 50 mL of ethanol, and a graphene dispersion with a concentration of 1 mg / mL was prepared under ultrasonic stirring. The prepared graphene dispersion and 10 g of natural graphite were added to a blender, and the stirring speed was adjusted to 30 r / min. After stirring for 0.5 h, a mixed solution was obtained. The drying temperature of the spray dryer was set to 250 ° C and the atomization frequency was 350 Hz. The obtained mixed solution was sucked into the spray dryer at a feed rate of 60 mL / min using a peristaltic pump for drying, and a graphene-coated natural graphite negative electrode material with a graphene oxide coating amount of 0.5% was obtained.

[0023] The obtained graphene oxide coated natural graphite negative electrode material was assembled into a battery, and the working electrode was prepared according to the ratio of sample: conductive agent acetylene black: polyvinylidene fluoride = 80:10:10, and the metal lithium sheet was used as the reference electrode to test its cycle performance. The test conditions were 25°C, current density 0.2C, and voltage range 0.01-2V.

[0024] As attached Figure 2 As shown, the obtained graphene oxide coated natural graphite negative electrode material has a reversible specific capacity of 370.1 mAh / g at a current density of 0.2 C. At a current density of 0.2 C, after 50 cycles, the reversible specific capacity is 363.9 mAh / g, and the capacity retention rate is 98.3%.

[0025] Example 2

[0026] Dissolve 0.5g of oxidized graphene in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 350Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 60mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 5%. At a current density of 0.2C, the reversible specific capacity is 387.1mAh / g. After 50 cycles, the reversible specific capacity is 376.2mAh / g, and the capacity retention rate is 97.1%.

[0027] Example 3

[0028] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 350Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 40mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 365.1mAh / g. After 50 cycles, the reversible specific capacity is 353.9mAh / g, and the capacity retention rate is 96.9%.

[0029] Example 4

[0030] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 350Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 80mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 367.1mAh / g. After 50 cycles, the reversible specific capacity is 352.8mAh / g, and the capacity retention rate is 96.1%.

[0031] Example 5

[0032] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 150℃ and the atomization frequency to 350Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 60mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 356.4mAh / g. After 50 cycles, the reversible specific capacity is 340.6mAh / g, and the capacity retention rate is 95.6%.

[0033] Example 6

[0034] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 350Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 60mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 369.5mAh / g. After 50 cycles, the reversible specific capacity is 358.0mAh / g, and the capacity retention rate is 96.9%.

[0035] Example 7

[0036] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 250Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 60mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 350mAh / g. After 50 cycles, the reversible specific capacity is 330.4mAh / g, and the capacity retention rate is 94.4%.

[0037] Example 8

[0038] Dissolve 0.05g of graphene oxide in 50ml of ethanol, prepare a graphene dispersion with a concentration of 1mg / mL under ultrasonic stirring, add the prepared graphene dispersion and 10g of natural graphite into a blender, adjust the stirring speed to 30r / min, and stir for 0.5h to obtain a mixed solution. Set the drying temperature of the spray dryer to 250℃ and the atomization frequency to 500Hz. Use a peristaltic pump to suck the obtained mixed solution into the spray dryer at a feed rate of 60mL / min for drying to obtain a graphene-coated natural graphite negative electrode material with a graphene coating amount of 0.5%. At a current density of 0.2C, the reversible specific capacity is 363.6mAh / g. After 50 cycles, the reversible specific capacity is 350.4mAh / g, and the capacity retention rate is 96.4%.

[0039] Part of the implementation of the invention has been specifically described above, but the present invention is not limited to the above-described embodiments. Those skilled in the art may make equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A method for preparing a graphene oxide-coated natural graphite negative electrode material, characterized in that The following steps are involved: Step (1) ultrasonically dissolving a certain mass of graphene oxide powder in a solvent to obtain graphene oxide dispersions of different concentrations. Step (2) The natural graphite and the graphene dispersion are fully mixed in a certain proportion to obtain a mixed solution. Step (3) The mixed solution obtained in step (2) is sucked into a spray dryer using a peristaltic pump, and dried at a certain temperature and atomization frequency to obtain a graphene oxide-coated natural graphite negative electrode material.

2. The method for preparing a graphene oxide-coated natural graphite negative electrode material according to claim 1, characterized in that: The number of graphene layers described in step (1) is 1-3 layers, the diameter of the layer is 0.5-20um, and the thickness is 0.5-3nm.

3. The method for preparing a graphene oxide-coated natural graphite negative electrode material according to claim 1, characterized in that The concentration of the graphene solution in step (1) is 0.2-5 mg / mL.

4. The method for preparing a graphene oxide-coated natural graphite negative electrode material according to claim 1, characterized in that The solvent in step (1) is water, ethanol or N-methylpyrrolidone.

5. The method for preparing a graphene oxide-coated natural graphite negative electrode material according to claim 1, characterized in that The mass ratio of graphene to natural graphite described in step (2) is (0.001-0.2):1.

Citation Information

Patent Citations

  • Method and application of graphene coated lithium-ion battery graphite negative electrode material

    CN108281634A

  • Preparation method of asphalt-coated spherical natural graphite negative electrode material

    CN111081989A

  • Preparation method of graphene-coated natural graphite negative electrode material

    CN113955747A